2015
DOI: 10.1021/acs.jnatprod.5b00276
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics-Driven Discovery of a Prenylated Isatin Antibiotic Produced byStreptomycesSpecies MBT28

Abstract: Actinomycetes are a major source of antimicrobials, anticancer compounds, and other medically important products, and their genomes harbor extensive biosynthetic potential. Major challenges in the screening of these microorganisms are to activate the expression of cryptic biosynthetic gene clusters and the development of technologies for efficient dereplication of known molecules. Here we report the identification of a previously unidentified isatin-type antibiotic produced by Streptomyces sp. MBT28, following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 63 publications
0
44
1
Order By: Relevance
“…PLS here acted as a supervised data reduction algorithm to study the correlation of the abundances of these 40 mass features ( X ‐variables) in total with exchange rate values ( Y ‐variables). A permutation test that is a calculation of quality of the fit and the predictive ability validated the supervised model (Wu et al ., ). The R 2 and Q 2 values for this PLS analysis were 0.98 and 0.88, respectively, indicating a favourable predictability and reproducibility.…”
Section: Resultsmentioning
confidence: 97%
“…PLS here acted as a supervised data reduction algorithm to study the correlation of the abundances of these 40 mass features ( X ‐variables) in total with exchange rate values ( Y ‐variables). A permutation test that is a calculation of quality of the fit and the predictive ability validated the supervised model (Wu et al ., ). The R 2 and Q 2 values for this PLS analysis were 0.98 and 0.88, respectively, indicating a favourable predictability and reproducibility.…”
Section: Resultsmentioning
confidence: 97%
“…2D NMR examination of co‐culture crude extracts confirmed that these two singlets belong to the same compound. NMR‐guided chromatographic fractionation was carried out to isolate the desired components . Fractions showing the target signals ( δ =2.45 and 2.42 ppm) were combined and further analyzed by 2 D NMR, including by COSY, 1 J ‐resolved, HSQC, and HMBC (Figures S1–S5 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…222-225 However, low abundance compounds can often be overlooked in complex extracts, and recently MVSA have been utilized to help link observed fraction bioactivity to detectable features from metabolomic analyses. 39,226 Even after correlating metabolites with biological activity, determining the mode of action for active compounds can be difficult and expensive. 227-230 One approach has been developed that uses the antibiotic spectrum of activities across different organisms, mode of action profiles (BioMAP), to group similar antibiotics.…”
Section: Investigations Of Secondary Metabolite Bioactivitymentioning
confidence: 99%